GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 117729 species occurrences available in GBIF matching the query: TaxonKey: 5204019. The dataset includes 117729 records from 189 constituent datasets: 29 records from Collection Pisces SMF. 32 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 3 records from Fish tag database. 91 records from Inland Fisheries Ireland data on freshwater fish in Irish lakes. 1 records from European Molecular Biology Laboratory Australian Mirror. 5 records from CSIRO Ichthyology provider for OZCAM. 1 records from Kohlstattbrunnental. 16 records from Fish Collection of Yokosuka City Museum. 5 records from Ichthyology. 1 records from BioGIS - Fish - INPA database. 6 records from Fish Specimens. 1 records from ArtenFinder. 8 records from Tasmanian Museum and Art Gallery provider for OZCAM. 7 records from Freshwater Fish Specimens of Lake Biwa Museum. 85 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 43 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from The Korean Freshwater Fishes. 1 records from Colección de Ictiología. 10 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 4 records from Colección Nacional de Peces del IBUNAM. 4 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 2 records from Bernice P. Bishop Museum. 154 records from North Carolina State Museum of Natural Sciences Fishes Collection. 62 records from Museum of Comparative Zoology, Harvard University. 1 records from National Taiwan University. 8 records from Atlantic Reference Centre (OBIS Canada). 2 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 73 records from Swedish Board of Fisheries (Fiskeriverket) - Swedish Electrofishing Registry. 2 records from Israel Nature and Parks Authority. 1 records from National Museum of Marine Biology and Aquarium. 478 records from Oregon State Ichthyology Collection. 11 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 2 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 2591 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 34 records from UNSM Vertebrate Specimens. 101 records from CUMV Fish Collection (Arctos). 3 records from Merseyside BioBank - Merseyside BioBank NBN Frequently Updated Taxa. 5 records from Colección de Peces Universidad Católica de Oriente. 7 records from Ichthyology, Kagoshima University Museum. 1155 records from Freshwater fishes of Italy. 1 records from Neckartalsüdhang (Horb). 1673 records from Atlas of Danish Fishes. 1 records from Ibaraki Nature Museum, Fish collection. 1 records from Stausee (Oberdigisheim/Meßstetten). 32 records from UAIC Ichthyological Collection. 10 records from Plan de vertebrados de la Patagonia. 46 records from Monitoring data from the federal state Hesse (Germany). 1 records from Gunma Museum of Natural History, Fish Specimen. 14 records from SBMNH Vertebrate Zoology. 1 records from Individual Sightings. 4 records from Staffordshire Ecological Record - SER Species-based Surveys. 13 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 151 records from Australian Museum provider for OZCAM. 12 records from Fish specimen database of Osaka Museum of Natural History. 4 records from Données ONF Faune-Flore-FOnge. 14 records from Museum of Zoology, University of Navarra. 91 records from University of Alberta Ichthyology Collection (UAMZ). 278 records from NINA Vanndata fisk. 19 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 53 records from Database Schema for UC Davis Wildlife museum. 12 records from Colección de peces y macroinvertebrados del Museo de Historia Natural de la Pontificia Universidad Javeriana. 2 records from Mammal and Fish speciemens of Kumamoto City Museum. 45 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 100 records from VIS - Fishes in inland waters in Flanders, Belgium. 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 8 records from Freshwater fish collection. 162 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 680 records from Ichthyology Collection - Royal Ontario Museum. 1 records from Ireland's BioBlitz. 4 records from Lund Museum of Zoology (MZLU). 136 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 11 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 10 records from TNHC Ichthyology Collection. 1 records from Schaalbach. 4 records from UMZC Zoological Specimens. 21 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 23 records from SA Fauna (BDBSA). 421 records from Environment Agency - Environment Agency Non-native Species records v1. 14 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 3 records from Fundación Miguel Lillo - Colección Ictiológica. 12 records from CSUC Vertebrate Collection. 12 records from UCM Fish Collection (Arctos). 8 records from Fish collection, Natural History Museum, University of Oslo. 940 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 30 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 154 records from NCSM Fishes Collection. 2 records from Taiwan Fisheries Research Institute – Digital archives of coastal and offshore specimens. 120 records from Royal Dutch Angling Association (SVN) - Piscaria. 4 records from Collection Ichthyologie - SNSD. 2 records from Bureau of Rural Sciences National commercial fisheries half-degree data set 2000-2002 (OBIS Australia). 2 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 10 records from Museum Victoria provider for OZCAM. 4 records from North Pacific Groundfish Observer (North Pacific Research Board). 2 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Ireland's BioBlitz 2012. 1 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 1 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 91 records from Artdata. 35 records from Especies de peces introducidas en aguas continentales de México. Catálogo y manuscrito. 1 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 1 records from IndOBIS, Indian Ocean Node of OBIS. 23 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 1 records from Queen Victoria Museum Art Gallery provider for OZCAM. 1 records from Fieldjournal.org observation database. 13 records from NRM-Fishes. 2 records from Anymals+plants - Citizen Science Data. 92 records from UF FLMNH Ichthyology. 1 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 5 records from UAFMC Fish. 26 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 169 records from Inventario Español de Especies Terrestres (MAGRAMA). 94 records from Monitoring data from the federal state Saxony (Germany). 324 records from UWFC Ichthyology Collection. 7 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 14461 records from Pacific Ocean Shelf Tracking (OBIS Canada). 3 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 7 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 13 records from FHSM Fish Collection. 17 records from BioGIS - Fish - HUJ collections. 56 records from MSB Host Collection (Arctos). 7 records from Western Australian Museum provider for OZCAM. 5 records from Queensland Museum provider for OZCAM. 82670 records from United States Geological Survey Nonindigenous Aquatic Species Database. 61 records from naturgucker. 5 records from The Fish Collection. 1 records from Rund um den Hainbergsee. 2 records from CNPE/Coleccion Nacional de Peces. 9 records from University of California Museum of Paleontology. 1 records from Zielbach (Töll). 1126 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 192 records from New Mexico Biodiversity Collections Consortium database. 13 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 29 records from Swedish Board of Fisheries (Fiskeriverket) - National Register of Survey testfishing. 1 records from MSB Mammal Collection (Arctos). 1 records from Tag der Artenvielfalt in der Stadt Luzern. 1 records from Freshwater fish Specimens of Taga Town Museum, Shiga Pref., Japan. 592 records from Fishbase. 86 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 132 records from Ohio State University Fish Division (OSUM). 2 records from Colección Ictiológica de la Universidad de Antioquia. 1416 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 7 records from Fish Collection of Hokkaido University. 8 records from Colección Ictiológica del CENPAT-CONICET. 14 records from Fish collection of National Museum of Nature and Science. 1 records from Fish Living in Freshwater (KIDR-PI). 1 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 161 records from Freshwater fishes of the Western Balkans. 26 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 49 records from Field Museum of Natural History (Zoology) Fish Collection. 882 records from Fish specimens. 3 records from MfN Fish Collection, Zoology. 40 records from AUM Fish Collection. 30 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 1 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 1 records from Brenz (Heidenheim). 129 records from Canadian Museum of Nature Fish Collection. 1 records from Mammal tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 1 records from Wanderweg am Windebyer Noor (bei Eckernförde). 5 records from WNMU Fish Collection (Arctos). 41 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 617 records from CAS Ichthyology (ICH). 30 records from UAM Fish Collection (Arctos). 12 records from Zoology (Museum of Evolution - Uppsala). 259 records from LACM Vertebrate Collection. 2 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 18 records from KUBI Ichthyology Collection. 1 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1851 records from NatureServe Network Species Occurrence Data. 54 records from Biological and palaeontological collection and observation data MNHNL. 1 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 24 records from South Australian Museum Australia provider for OZCAM. 4 records from Donnees ONF Faune-Flore-Fonge. 77 records from Tulane University Museum of Natural History. 1 records from Mangfalltal. 106 records from iNaturalist research-grade observations. 88 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 16 records from Colección Ictiológica del Instituto Alexander von Humboldt. 192 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 576 records from NMNH occurrence DwC-A. 2 records from University of Ghent - Zoology Museum - Vertebratacollectie. 70 records from SAIAB. 2 records from Clare Biological Records Centre dataset. 46 records from Natural History Museum (London) Collection Specimens. 7 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 4 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 26 records from Geographically tagged INSDC sequences. 16 records from Diveboard - Scuba diving citizen science observations. 1 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 1 records from Hamberger Brücke / Würmtal (Pforzheim).
Keywords: GBIF; biodiversity; species occurrences